1995
DOI: 10.1101/lm.2.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a calcium-binding protein, S100 beta, in astrocytes alters synaptic plasticity and impairs spatial learning in transgenic mice.

Abstract: R o b e r t G e r l a i , 1'4 J. M a r t i n W o j t o w i c z , 2 A l e x a n d e r M a r k s , 3 a n d J o h n R o d e r 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 42 publications
3
80
0
2
Order By: Relevance
“…They received two sessions (90-min intersession interval) of three trials (maximum trial length 60 s, 40-min intertrial interval) each day between 10:00 and 17:00 h. Latency to escape (seconds) onto the platform was recorded. The platform size was decreased between the 1st, 2nd and 3rd day (diameter being 20, 15, 10 cm, respectively) [22]. After the hidden platform training, a probe trial was administered during which the platform was removed from the tank and the swimming pattern of the mice was video-recorded for 60 s. The relative duration of time (%) the mice spent in four equal quadrants of the tank, the number of exact platform location crossings, average swimming speed (cm/s) during the first ten bouts of swimming, and the duration spent with floating motionless in the tank were measured with an event recorder computer program [24].…”
Section: Beha6ioral Apparatus and Proceduresmentioning
confidence: 98%
See 2 more Smart Citations
“…They received two sessions (90-min intersession interval) of three trials (maximum trial length 60 s, 40-min intertrial interval) each day between 10:00 and 17:00 h. Latency to escape (seconds) onto the platform was recorded. The platform size was decreased between the 1st, 2nd and 3rd day (diameter being 20, 15, 10 cm, respectively) [22]. After the hidden platform training, a probe trial was administered during which the platform was removed from the tank and the swimming pattern of the mice was video-recorded for 60 s. The relative duration of time (%) the mice spent in four equal quadrants of the tank, the number of exact platform location crossings, average swimming speed (cm/s) during the first ten bouts of swimming, and the duration spent with floating motionless in the tank were measured with an event recorder computer program [24].…”
Section: Beha6ioral Apparatus and Proceduresmentioning
confidence: 98%
“…In addition to the above tests, GluR2 null mutant and age-matched control mice were tested in two paradigms of the Morris water maze as described previously [18,22]: the hidden platform task (spatial learning test) and a visible platform task (non-spatial learning test). A white acrylic circular tank (diameter 120 cm, height 30 cm) was filled with water (239 1°C) made opaque with a non-toxic white color 'tempera'.…”
Section: Beha6ioral Apparatus and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Some animal studies found that transgenic mice with overexpression of the human S100B gene exhibited impaired spatial ability [8], whereas mutant mice with null-expression of the S100B gene exhibited enhanced spatial ability [17]. Both of these findings strongly indicated that S100B may modulate spatial ability.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The elevated levels of S100B in neurodegenerative models have been found to be associated with impairments in learning and memory function. 13,14 In addition, recently an association between elevated circulating S100B levels and impaired neurologic outcomes has been observed after clinical brain injury. 5,15 Studies suggest that cellular signaling resulting from the interaction of S100B with AGER may be responsible for its proinflammatory effects.…”
Section: Introductionmentioning
confidence: 99%